Follow the Money: Does the Financial Sector Intermediate Natural Resource Windfalls? - Thorsten Beck; Steven Poelhekke (Center for Economic Studies and ifo Institute (CESifo), 2017)
The need to absorb windfalls gains and manage them appropriately has been discussed extensively by academics and policy makers alike. We explore the role of the financial sector in intermediating these windfalls. Controlling for the level of financial development, inflation, GDP growth and country fixed-effects, we find a relative decline in financial sector deposits in countries that experience an unexpected natural resource windfall as measured by shocks to exogenous world prices. Moreover, we find a similar relative decline in lending, which is mostly due to the decrease in deposits. The smaller role for the financial sector in intermediating resource booms is accompanied by a stronger role of governments in channeling resources into the economy, mostly through higher government consumption.
Keywords: E20; F41; G20; O10; Q32; Q33; 330; natural resources; financial development; banking